MADRASAH SEBAGAI LEMBAGA PENDIDIKAN ISLAM (Sistem dan Perkembangannya Sebelum dan Sesudah Kemerdekaan) - Rahmat, Rahmat (RIHLAH, 2014)
Madrasahis analternativeeducational institutionfor the parentstobethe venue forthe education ofherson. The number ofmadrasahfromone period to thenext governmenthas developed. Therefore,policy makersand others involvedin the educational processat the schoolshouldpay attention tothe learning systemasthe early history ofits formation.The Grow thmadrasa hin Indonesia against the back dropof twofactors; First, factors renewal of Islamic thought which responded by breathing santri who studied in the Middle East. The second is response to the Dutch governments education policy. The development of madrasah before and after independence is determined policy authorities. Before independence policies adopted bythe colonial government to wards education oriented to strengÂ  the rule of Islam in Indonesia. After independence, the Indonesian government to law the madrasah education with a number of regulations and legislation